2016
DOI: 10.1371/journal.pgen.1006256
|View full text |Cite|
|
Sign up to set email alerts
|

The Musashi 1 Controls the Splicing of Photoreceptor-Specific Exons in the Vertebrate Retina

Abstract: Alternative pre-mRNA splicing expands the coding capacity of eukaryotic genomes, potentially enabling a limited number of genes to govern the development of complex anatomical structures. Alternative splicing is particularly prevalent in the vertebrate nervous system, where it is required for neuronal development and function. Here, we show that photoreceptor cells, a type of sensory neuron, express a characteristic splicing program that affects a broad set of transcripts and is initiated prior to the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
122
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(135 citation statements)
references
References 78 publications
13
122
0
Order By: Relevance
“…For example, it may be useful to transiently enhance Musashi function when enlarging stem or progenitor pools for therapeutic purposes, such as bone marrow replacement. As other examples, MSI1 is induced as part of the damage response process in models for arthritis(85), elevated in atherosclerotic plaques(86), and critical for survival of photoreceptors and appropriate cell function in the retina (71,87). Clearly, more work is needed to refine the role of MSI proteins in these and other tissues, with the goal of ameliorating pathologic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it may be useful to transiently enhance Musashi function when enlarging stem or progenitor pools for therapeutic purposes, such as bone marrow replacement. As other examples, MSI1 is induced as part of the damage response process in models for arthritis(85), elevated in atherosclerotic plaques(86), and critical for survival of photoreceptors and appropriate cell function in the retina (71,87). Clearly, more work is needed to refine the role of MSI proteins in these and other tissues, with the goal of ameliorating pathologic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Connecting Musashi proteins to control of miRS, discrete LIN28-binding motif has been identified in the C-terminus of MSI1 (9): while this motif is absent in MSI2, recent studies have nevertheless shown biological activity of MSI2 in regulating Lin28A (23,61). Additionally, both MSI1 and MSI2 have been described to regulate alternative splicing in mouse retinal photoreceptor and neural stem cells, with mechanisms still to be exactly defined (54,71). Understanding how the protein structure and signaling downstream of MSI1 and MSI2 are linked to their function in different cellular contexts remains an important area for future work.…”
Section: Mechanisms Of Post-transcriptional Regulation By Musashi Promentioning
confidence: 99%
“…This implies that CWC27 exerts functions essential for both early tissue development and later functional maintenance. Furthermore, the non-syndromic RP-affected case subject in family 3 also shows that the mature retina, with a high rate of protein turnover and extensive alternative splicing, [55][56][57] is particularly vulnerable to perturbations of spliceosome assembly and functions. In addition, we observed some family-specific symptoms outside the above-mentioned two phenotypic domains, such as ectodermal defects in family 4 and internal organ anomalies in families 5 and 6, suggesting that CWC27 may play important roles in additional tissues.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies however suggest the molecular function of MSI proteins may be far more complex than translational inhibition. The Msi family has been implicated in controlling polyadenylation of specific mRNAs in Xenopus oocytes, alternative splicing in photoreceptor cells and neurons, and message stabilization as well as translational potentiation by MSI has been suggested 1014 . Despite our lack of understanding regarding the molecular underpinnings of target regulation by MSI proteins, their importance in governing stem cell activity and oncogenesis has become increasingly clear from studies focusing on the hematopoietic system and intestinal epithelium- two high-turnover tissues with well-defined stem cell compartments prone to oncogenic transformation.…”
Section: Msi Rbp Family Of Post-transcriptional Regulatorsmentioning
confidence: 99%